The effect of environmental factors and hormone treatments on ovulation rate and spawning success in cardinal tetras, Paracheirodon axelrodi (Pisces: Characidae) - Burton, Simon Mark (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1998)
Cardinal tetras, Paracheirodon axelrodi (Pisces: Characidae), are among the most popular tropical ornamental fish in the world. Millions of cardinal tetras are removed from their natural habitat, the upper tributaries of the Rio Negro in Brazil, each year and exported to North America and Europe where they are abundantly available at low cost. This, combined with the fact that they do not spawn freely in captivity has excluded any incentive to culture this fish on a commercial scale in these areas. However, the demand for cardinal tetras in South Africa is high, but their availability is limited to sporadic imports of wild caught fish which has resulted in an increase in their relative value. Thus, there is an appreciable incentive to investigate methods for inducing this species to reproduce in captivity. Information on methods for inducing spawning would form an integral part of a potential production plan for the culture of this species in South Africa. This study consisted of a number of experiments designed to investigate factors related to the spawning of cardinal tetras in captivity. The first series of experiments investigated the effect of variables such as the water chemistry of the experimental system, the sex ratio of the fish, the effect of conditioning and the effect of different spawning media on spawning success. The second series of experiments tested the effects of various environmental stimuli or hormonal treatments on spawning in cardinal tetras. Environmental stimuli tested included a rise in temperature, a rise in water level and a fresh rain water flush. Hormonal treatments included feeding GnRHa enriched brine shrimps to the fish or the application of hormone injections (hypophysation). Neither environmental stimuli nor brine shrimp enrichment induced cardinals to spawn in a repeatable manner. The same was true for hypophysation, but in this case a low incedence of ovulation of injected females was observed. Oocytes from ovulated and non-ovulated females were examined under a microscope and from this it was determined that cardinal tetras are group synchronous spawners, containing two distinct cohorts of oocytes in the ovary. The effect of a number of environmental stimuli on ovulation rate in cardinal tetras were then tested but did not induce ovulation in any females. A series of three experiments was performed investigating the effect of conditioning the sexes together on ovulation rate and spawning success. Conditioning the sexes together had no effect on spawning success, but a significantly higher ovulation rate was observed in females that vvere conditioned together with males. Male cardinals did not follow this trend and lost condition when conditioned together with females. The next experiment tested if pheromones from red serpae tetras, Hyphessobrycon serpae, could be used to induce ovulation and spawning in cardinal tetras. This was found not to be the case. The final series of experiments tested the effect of Aquaspawn® enriched Artemia on ovulation rates in female cardinal tetras. Aquaspawn® is a water soluble preparation of GnRHa and dopamine. Aquaspawn® enriched Artemia were found to be effective for inducing female cardinal tetras to ovulate. However, the results from this method of enrichment were not entirely reliable and further research is warranted. Finally, a protocol for evaluating spawning in topical, freshwater egg-laying fish was proposed, based on the results from this study. The advantages and disadvantages of such a protocol were discussed.
Keywords: Characidae; Characidae -- Breeding; Tropical fish -- Breeding; Fishes -- Induced spawning; Characidae -- Spawning